In-hospital Outcomes of Rotational Atherectomy in ST-Elevation Myocardial Infarction: Results From the Multicentre ROTA-STEMI Network - Hemetsberger, Rayyan; Mankerious, Nader; Muntané-Carol, Guillem; Temporal, Justin; Sulimov, Dmitriy; Gaede, Luise; Woitek, Felix; Grau, Edgar Fadeuilhe; Scalamogna, Maria; Olschewski, Maximilian; Mitsis, Andreas; Ruzsa, Zoltán; et al. (Canadian Journal of Cardiology, 2024)
Background: Although the use of rotational atherectomy (RA) is off-label in the setting of ST-elevation myocardial infarction (STEMI), it can be the only option in severely calcified culprit lesions to achieve procedural success. We sought to investigate the safety and feasibility of RA during primary percutaneous coronary intervention (PPCI). Methods: This was a retrospective observational study of patients who underwent RA during PPCI from 12 European centres. The main outcomes were procedural success (defined as successful stent implantation with final thrombolysis in myocardial infarction [TIMI] flow 3 and residual stenosis < 30%) and in-hospital mortality. A comparison of patients presenting with and without shock was performed. Results: In 104 patients with RA during STEMI, the mean age was 72.8 ± 9.1 years, and 35% presented with cardiogenic shock. Bailout RA was performed in 76.9% of cases. Mean burr size was 1.42 ± 0.21 mm. Procedural success was achieved in 86.5% of cases, with no difference between shocked and nonshocked patients (94.4% vs 82.4%; P = 0.13). In-hospital stent thrombosis occurred in 0.96%, perforation in 1.9% and burr entrapment in 2.9% of cases. In spite of equally high procedural success, in-hospital mortality was higher in shocked (50%) compared with nonshocked patients (1.5%; P < 0.0001). Conclusions: Patients presenting with STEMI requiring RA, represent a high-risk population, frequently presenting with cardiogenic shock. In this analysis of selected patients, RA was performed as a bailout strategy in the majority, and, as such, RA seems to be feasible with a high procedural success rate. In the absence of cardiogenic shock, RA-facilitated PCI seems to be associated with low in-hospital mortality.
CRIS-Team Scopus Importer:2024-05-03